Metachronous Rectum Metastases from Gastric Adenocarcinoma: A Case Report - Deniz Tural; Fatih Selçukbiricik; Abdülkadir Erçalışkan; Berin İnanç; Feray Günver; Evin Büyükünal (Case Reports in Medicine)
Introduction. Hepatic metastases of gastric adenocarcinomas are frequently observed due to the drainage into portal vein. Intestinal metastases disseminate from gastrocolic and mesenteric ligaments but they are seen very rarely and in most cases detected in postmortem studies. Case Report. A 74-year-old female patient with no known history of disease. Her complaints on application were epigastric pain, burning, and constipation. Gastroscopy showed a submucosal mass in the greater curvature of fundus and in colonoscopy, a mass with polypoid appearance that narrows the lumen at the rectum was detected. No far metastases or pathology were detected. Pathology report from gastric biopsy material demonstrated well-differentiated adenocarcinoma. Cytokeratin 7 (CK7) was found to be extensively strongly positive, Cytokeratin 20 (CK20) was negative in the immunohistochemical staining of the biopsy obtained from rectosigmoid area. Conclusion. Gastric cancer is among the frequent cancers today, most of which are adenocarcinomas. Although most of the metastases are observed in the liver, lungs, lymph nodes, and peritoneum, it should be remembered that intestinal metastases may be seen without the presence of any other metastatic focus. Our case is the first in literature reporting a rectum metastasis without any other organ metastasis.